Peningkatan Hasil Belajar Pendidikan Agama Katolik melalui Metode Scientific di Kelas II SD Cirebon - Agnes Sri Antari; Romo FX. Sugiyana (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the extent to which learning outcomes in Catholic Religious Education and Character Education can be improved through the application of the scientific learning method among second-grade students at SD Santa Maria Cirebon. The learning materials focused on the topics “My Parents,” “The Role of Family Members,” and “Playing with Friends.” The research subjects consisted of 20 second-grade students, while the object of the study was their learning outcomes following the implementation of the scientific learning method. This method encourages students to actively observe, question, experiment, reason, and communicate their learning outcomes independently and responsibly. The research was conducted over three cycles, each including planning, implementation, observation, and reflection stages. The results indicated a significant improvement in students' learning outcomes. In the first cycle, the average student achievement was 75%, which increased to 85% in the second cycle and reached 100% in the third cycle. In addition to cognitive development, there was also notable improvement in social aspects such as independence, responsibility, and discipline. The number of students showing positive development increased from 75% in the first cycle to 95% in the second cycle, and further to 98% in the third cycle. These findings suggest that the scientific learning method is effective in enhancing both academic performance and social character in Catholic Religious Education and Character Education. Therefore, it is recommended that this method be more widely applied in similar learning contexts.